3x-4(-2x-5)=2x-3

Simple and best practice solution for 3x-4(-2x-5)=2x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4(-2x-5)=2x-3 equation:


Simplifying
3x + -4(-2x + -5) = 2x + -3

Reorder the terms:
3x + -4(-5 + -2x) = 2x + -3
3x + (-5 * -4 + -2x * -4) = 2x + -3
3x + (20 + 8x) = 2x + -3

Reorder the terms:
20 + 3x + 8x = 2x + -3

Combine like terms: 3x + 8x = 11x
20 + 11x = 2x + -3

Reorder the terms:
20 + 11x = -3 + 2x

Solving
20 + 11x = -3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
20 + 11x + -2x = -3 + 2x + -2x

Combine like terms: 11x + -2x = 9x
20 + 9x = -3 + 2x + -2x

Combine like terms: 2x + -2x = 0
20 + 9x = -3 + 0
20 + 9x = -3

Add '-20' to each side of the equation.
20 + -20 + 9x = -3 + -20

Combine like terms: 20 + -20 = 0
0 + 9x = -3 + -20
9x = -3 + -20

Combine like terms: -3 + -20 = -23
9x = -23

Divide each side by '9'.
x = -2.555555556

Simplifying
x = -2.555555556

See similar equations:

| 5x^2+6-51=0 | | h-4+1=3 | | 8(3x-5)=-64 | | ln(17+2x)=2ln(x+1) | | 7/7=3 | | -2x-5(4x+3)=3x | | 26=10h/18 | | 11.5x+12=161.50 | | 3(-2y)+7y=1 | | 5t=56 | | c=12+11.5t | | 9x-6(x-2)=6+x+20 | | (9x-6)+(-8x+4)=7 | | 2x+x^2=0.051216343 | | sqrt(60)*sqrt(y/4) | | v/9=3/7 | | (4a+4b+4c)(4a+4b+4c)= | | 86=-5-7(-4n-5) | | 30+50x=65x | | 17.42(p)=8.71 | | 4.13-0.54x=5x-2.795 | | 2w+8x-15y+7w+7x+8y= | | 3(1+-0.5y)+4y=-7 | | 5x+4y+9=0 | | x+16-64= | | x*(3x)^1/2 | | 3C^3-24= | | 2x-7/3=-3 | | 2x-7/7=-3 | | x-4/4=9 | | ((7x-1)^(1/2))^2 | | -3/42-x/53/4 |

Equations solver categories